ILRI research perspectives on livestock goods and bads - International Livestock Research Institute (International Livestock Research Institute, 2010)
Livestock Goods and Bads: Five ILRI theme leaders and scientists outline research objectives for 2010. Recorded at the ILRI Annual Program Meeting, Addis Ababa, 14-17 April 2010.